2012
DOI: 10.1029/2012ja017891
|View full text |Cite
|
Sign up to set email alerts
|

Identification of large‐scale billow‐like structure in the neutral sodium layer over Arecibo

Abstract: [1] We present a rare event that was recorded over Arecibo using sodium (Na) lidar. Billow-like structures with periods of $60 min were seen in the Na layer above 102 km on the night of 7-8 July 2010. The absence of any high-altitude structure was noted on the following night. Spectral analysis using the Lomb-Scargle technique reveals periods with larger power on the first night as compared to the adjacent one. The keograms derived from a sequence of 557.7 nm airglow images show the passage of a large frontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…Sarkhel et al (2012a) observed similar billow-like structures in the Na layer over Arecibo, Puerto Rico. They concluded that strong wind shear made the region dynamically unstable and was likely responsible for the observed structure in the Na layer that were observed in the lidargram for about 3 h. This structure -while still evolving -would likely be transported some distance by the overall background wind.…”
Section: Role Of Dynamical Instability and Advectionsupporting
confidence: 52%
See 4 more Smart Citations
“…Sarkhel et al (2012a) observed similar billow-like structures in the Na layer over Arecibo, Puerto Rico. They concluded that strong wind shear made the region dynamically unstable and was likely responsible for the observed structure in the Na layer that were observed in the lidargram for about 3 h. This structure -while still evolving -would likely be transported some distance by the overall background wind.…”
Section: Role Of Dynamical Instability and Advectionsupporting
confidence: 52%
“…That is, any structure related to Na + ions will map into the neutral Na layer on a few hour time scale. Sarkhel et al (2012a) observed high altitude (>102 km) billows in the neutral Na layer wherein they discussed that such structures in the neutral Na layer can be associated with the underlying ion layer during strong E S events for which ion concentration often exceeds 10 4 ions.cm −3 . In the intermediate altitude region (90 to 100 km), we encounter the most complex interaction with both neutral Na and Na ions playing comparable roles.…”
Section: Role Of Sporadic-e Activitymentioning
confidence: 99%
See 3 more Smart Citations